Examining the relationship between shame and social anxiety disorder: A systematic review. (December 2021) - Swee, Michaela B.; Hudson, Chloe C.; Heimberg, Richard G.
Abstract: This paper is the first systematic review of the literature on the relationship between shame and social anxiety (SA). We reviewed a total of 60 peer-reviewed empirical articles that met criteria for inclusion. We begin by summarizing literature investigating the empirical association between shame and SA and review literature on whether this association is impacted by cultural or diagnostic differences. Next, we briefly describe the updated version of Rapee and Heimberg's (1997) cognitive-behavioral model of social anxiety disorder (SAD; Heimberg, Brozovich, & Rapee, 2014) and propose how shame may interact with five processes described therein: environmental experiences, observations/images of the self, perceived negative evaluation by others, post-event cognitive processes, and behavioral manifestations of SA. We review the current literature on shame and SA as it relates to each of these domains. Thereafter, we discuss existing research on the role of shame in the treatment of SAD and the implications of the research discussed in this review. Finally, we conclude with a discussion of some key limitations in the existing literature and areas for future research. Highlights: Reviewed the literature on the relationship between shame and social anxiety (SA). Proposed shame's relevance to cognitive-behavioral models of SA. Most studies reviewed found a significant positive correlation between shame and SA. Shame may be related to the etiology and maintenance of SA. Treatment implications for social anxiety disorder are discussed.